The ontological nature of the categories - A. Casanova, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This paper contains a research on the ontological nature of the categories. It examines four theses: (a) that categories are linguistic, (b) that they are merely logical, (c) that all of them are real and (d) that some are real and some are logical but grounded in reality. It proves that the fourth thesis is the correct one and demonstrates some of its most significant presuppositions, developments and implications.